A textual history of Cicero's Academici libri - Hunt, Terence J. (Mnemosyne, Supplements, 1998)
This book addresses the problems surrounding Cicero's Academici Libri , including why the work exists in two different editions, why and when the work became fragmentary, and how it managed to survive. It achieves this by tracing the history and influence of the work from Antiquity to the present day. The main part of the book studies the manuscript tradition of the work. All extant manuscripts are fully described and their textual relationships are established. Historical information is assessed in order to show the part which manuscripts played in intellectual life, conclusions are reached on the archetype of the work and a full stemma of the tradition is built. The book contains a wealth of bibliographical information and will serve as a base for further study in the transmission of Cicero's works.